2013
DOI: 10.1186/1471-2407-13-380
|View full text |Cite|
|
Sign up to set email alerts
|

Nrf2 is required to maintain the self-renewal of glioma stem cells

Abstract: BackgroundGlioblastomas are deadly cancers that display a functional cellular hierarchy maintained by self-renewing glioma stem cells (GSCs). Self-renewal is a complex biological process necessary for maintaining the glioma stem cells. Nuclear factor rythroid 2-related factor 2(Nrf2) plays a significant role in protecting cells from endogenous and exogenous stresses. Nrf2 is a key nuclear transcription factor that regulates antioxidant response element (ARE)-containing genes. Previous studies have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 48 publications
4
81
0
Order By: Relevance
“…However, in response to cellular stress, Nrf2 isolates from Keap1, translocates to the nucleus, and up-regulates ARE-dependent gene expression [21]. These genes are related to a variety of proteins including antioxidant proteins, transport proteins, phase II detoxification enzymes, growth factors, proteasome subunits, drug-metabolizing enzymes, and multidrug-resistant protein-3 [5,[22][23][24]. Expression of these Nrf2-dependent proteins is crucial for survival and growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in response to cellular stress, Nrf2 isolates from Keap1, translocates to the nucleus, and up-regulates ARE-dependent gene expression [21]. These genes are related to a variety of proteins including antioxidant proteins, transport proteins, phase II detoxification enzymes, growth factors, proteasome subunits, drug-metabolizing enzymes, and multidrug-resistant protein-3 [5,[22][23][24]. Expression of these Nrf2-dependent proteins is crucial for survival and growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Berberat et al [26] reported that suppression of the Nrf2 target HO-1 using siRNA caused a decrease in proliferation and the increased sensitivity to gemcitabine in pancreatic cancer. In GBs, Nrf2 is required to maintain the self-renewal of glioma stem cells, and its down-regulation can inhibit tumor growth and invasiveness [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al revealed that knockdown of Nrf2 inhibited the proliferation of glioma stem cells and significantly reduced the expression levels of BMI-1, Sox2 and cyclin E (70).…”
Section: Signaling Pathways Of Bmi-1 In the Regulation Of Cancer And mentioning
confidence: 99%
“…Nrf2 is a TF that efficiently combats oxidative stress and may thus be utilized to enhance stem cell survival [65].…”
Section: Chapter III Promoting Survival Of Human C-kit+ Cpcsmentioning
confidence: 99%